MOTIVASI AGAMA DALAM TRADISI ARISAN MASYARAKAT BETAWI - Ilim Abdul Halim (Tatar Pasundan: Jurnal Diklat Keagamaan, 2020)
Generally, local traditions in urban areas are regressed or extinct along with modernization or globalization processes. But the tradition that is still maintained by a group of people can be found in Kampung Ceger RW 18 Jakasetia Bekasi City. Arisan tradition in this village is motivated by religious factors, Islam. This research analyzes the perpetrators and the tradition values that are oriented on Islamic teachings and its role in Arisan tradition. The phenomenon of Arisan in Betawi community can be analyzed with the motivation theory of Max Weber. The results show the Arisan tradition has religious motivation. The religious motivation element is the Betawi’s existence who belongs to the group Raden and Kai (ordinary people) as perpetrators. Other observed elements are togetherness, reciprocity, watchful, and mutually beneficial. These values are in accordance with Islamic teachings, such as solidarity and righteousness. Thus, the values legitimize Arisan tradition in the Betawi community.Key words: Motivation; Islam; Arisan; Betawi